Complete genome sequence of Mesorhizobium australicum type strain (WSM2073T). Issue 2 (September 2013) - Reeve, Wayne; Nandasena, Kemanthi; Yates, Ron; Tiwari, Ravi; O'Hara, Graham; Ninawi, Mohamed; Gu, Wei; Goodwin, Lynne; Detter, Chris; Tapia, Roxanne; Han, Cliff; Copeland, Alex; et al.
Abstract Mesorhizobium australicum strain WSM2073T was isolated from root nodules on the pasture legumeBiserrula pelecinus growing in Australia in 2000. This aerobic, motile, gram negative, non-spore-forming rod is poorly effective in N2 fixation onB. pelecinus and has gained the ability to nodulateB. pelecinus followingin situ lateral transfer of a symbiosis island from the original inoculant strain for this legume, Mesorhizobium ciceri bv.biserrulae WSM1271. We describe that the genome size ofM. australicum strain WSM2073T is 6, 200, 534 bp encoding 6, 013 protein-coding genes and 67 RNA-only encoding genes. This genome does not contain any plasmids but has a 455.7 kb genomic island fromMesorhizobium ciceri bv.biserrulae WSM1271 that has been integrated into a phenylalanine-tRNA gene.